Penyelesaian Sengketa Penolakan Proyek PLTP Bedugul Melalui Gugatan Perbuatan Melanggar Hukum Oleh Badan Dan/Atau Pejabat Pemerintahan (Onrechtmatige Overheidsdaad) - Verdad Chabibullah Abdallah Iman; Maret Priyanta; Dicky Muslim (KRTHA BHAYANGKARA, 2023)
During the implementation of the Bedugul Geothermal Power Plant (PLTP) project, Bali received protests from the Balinese people which has caused the project to be neglected until now. In addition to the rejection from the Balinese people, the Government of Bali also refused to continue the Bedugul PLTP geothermal project, where the refusal was stated in the juridical provisions of the Governor of Bali's Rejection Letter Number 660.1/1497/Bid.1/Bapedalda dated 17 October 2005 addressed to the Minister of Energy and Mineral Resources Mineral Resources and Bali Governor Regulation No. 45 of 2019 concerning Bali Clean Energy which emphasizes that PLTP construction cannot be carried out in the Bedugul sacred area and indirectly this has hampered geothermal permits in the Bedugul working area. The approach method used in this legal research is a normative juridical approach, research that is based on existing legal principles and also looks at the facts that occur. The results of this research reveal that the case of rejection of the Bedugul PLTP project by the Bali Regional Government can be resolved through a lawsuit  regarding unlawful act by government agencies and/or officials (onrechmatige overheidsdaad) with regard to the requirements for submitting administrative procedure at first as stated in Article 75 paragraph (1) of the Law Number 30 of 2014 concerning Government Administration.